Niko Chavchavadze on culture, values and aesthetics - Vladimer Luarsabishvili (Revista de Filosofía, 2023)
My purpose in this paper is to introduce some ideas of Georgian philosopher Niko Chavchavadze to a large audience. In particular, I focus on three issues: the complex structure of culture and the necessity of its definition; different types of values as basic components of culture; and Aesthetic as a specific form of reflecting reality. In relating these concerns to the ideas of Donald R. Kelly regarding the necessity of defining the nature of culture, as well as to the theories of values of Geert Hofstede and Shalom Schwartz, I indicate how Chavchavadze’s definitions and characterizations of the above-mentioned concepts anticipate contemporary approaches to these questions. In conclusion, I describe the current significance of Chavchavadze’s ideas and their possible role in the formation of civic society.